A Content Analysis of English Textbook Pathway to English Phase E Used in First Grade Senior High School - Fariz Adicahyo Bimantoro; Sri Handayani; Imroatul Ma’fiyah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The objective of the study was to identify the content analysis according to Cunningsworth’s theory in the English textbook entitled “Pathway To English Phase E” used in first grade senior high school by Th.M. Sudarwati and Eudia Grace. This study was a descriptive qualitative research with a documentation technique as a data collection method. This study also used triangulation namely triangulation of data. This study used content analysis according to Cunningsworth’s theory to analyzed the data. According to the criteria for selecting a good textbook which are: 1) aims and approaches, 2) language and content, 3) skill, 4) topic, and 5) methodology. The research was conducted from Desember 2023 to January 2024. This study was conducted at the library. To analyze the data, the researchers used qualitative analysis data. The results of this study will be the criteria for a good textbook according to cunningsworth 5 out of 8 criteria are present. Among them are aims and approaches, language and content, skill, topic and methodology. The research show aims and approaches get 93,75%, language and content get 70,83%, skill get 95,83%, topic get 87,5 and methodology get 100%. The average points is 89,5%. Additionally, the study shows that data is transmitted in the form of texts, instructions and conversations.